Graphene oxide – the nanomaterial for manufacturing semipermeable membranes - Bodzek , Michał; Konieczny , Krystyna (Instal, 2020)
In this paper methods of synthesis of membranes containing graphene and its derivatives, their properties and application areas are discussed. Chemical and physical functions of graphene and graphene oxide influencing water desalination efficiency and antifouling properties are also described. The article shows the methods of graphene functionalization and its derivatives, increasing the stability of the active layer, salt retention, permeability of water and the ion transport mechanism and reduction of fouling. Membranes made of these materials enable to obtain significantly higher water/permeate fluxes than in the case of currently used thin film composite polyamide membranes.